Recognition of oxidatively damaged erythrocytes by a macrophage receptor with specificity for oxidized low density lipoprotein. - Sambrano, G R (1994)
Macrophages specifically bind and internalize oxidatively modified low density lipoprotein (LDL) via the acetyl-LDL receptor and possibly one or more additional receptors jointly designated here as scavenger receptors. It is well accepted that these receptors are intimately involved in the formation of foam cells during atherogenesis. However, the normal physiological or pathophysiological role for these receptors has not been established. Oxidation of plasma membranes is a common accompaniment of cell damage and senescence. In particular, aged erythrocytes demonstrate peroxidation of their cell membrane lipids. In the present studies we show that oxidized human erythrocytes (treated with copper plus ascorbate or hydrogen peroxide) are bound and phagocytosed by mouse peritoneal macrophages in the absence of opsonizing antibodies. There was little or no binding of untreated erythrocytes. Oxidized LDL, but not acetylated or native LDL, inhibited this binding and uptake of oxidized erythrocytes. Inhibitors of scavenger receptor binding, including polyinosinic acid and fucoidin, also prevented binding of the oxidized red blood cells. We suggest that oxidative damage of erythrocytes results in the formation of lipid-protein conjugate(s) closely related to some of the conjugates found in oxidized LDL, making the oxidized erythrocyte a ligand for the macrophage scavenger receptors, apparently at a site distinct from that responsible for the binding of acetylated LDL. Oxidative modification of plasma membranes may represent a general mechanism that marks damaged cells for phagocytosis by macrophages.